2017
DOI: 10.1038/s41598-017-05483-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise initiates mechanistic target of rapamycin (mTOR) translocation and protein complex co-localisation in human skeletal muscle

Abstract: The mechanistic target of rapamycin (mTOR) is a central mediator of protein synthesis in skeletal muscle. We utilized immunofluorescence approaches to study mTOR cellular distribution and protein-protein co-localisation in human skeletal muscle in the basal state as well as immediately, 1 and 3 h after an acute bout of resistance exercise in a fed (FED; 20 g Protein/40 g carbohydrate/1 g fat) or energy-free control (CON) state. mTOR and the lysosomal protein LAMP2 were highly co-localised in basal samples. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
135
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(152 citation statements)
references
References 49 publications
15
135
2
Order By: Relevance
“…Recently, however, Korolchuk et al (15) reported that the cellular localisation of these mTOR/lysosomal complexes play a pivotal role in mTOR activation. In support of this hypothesis, we recently reported that a single bout of resistance exercise initiated mTOR/lysosome translocation to the cell periphery, and occurred in parallel to an increase in mTOR activity and interaction between mTOR and proteins involved in translation initiation (23).…”
Section: Introductionmentioning
confidence: 69%
“…Recently, however, Korolchuk et al (15) reported that the cellular localisation of these mTOR/lysosomal complexes play a pivotal role in mTOR activation. In support of this hypothesis, we recently reported that a single bout of resistance exercise initiated mTOR/lysosome translocation to the cell periphery, and occurred in parallel to an increase in mTOR activity and interaction between mTOR and proteins involved in translation initiation (23).…”
Section: Introductionmentioning
confidence: 69%
“…As a nodal sensor and integrator of environmental cues for organismal growth and homeostasis, the mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) is particularly relevant since an acute muscle contraction increases phosphorylation of mTOR at Ser‐2448, downstream p70S6 kinase‐1 (S6K1) at Thr‐389 and rpS6 at Ser‐240/244 along with increased protein synthesis . Importantly, mTORC1, but not mTORC2, is critical for maintaining muscle mass and metabolic function, and activation of mTORC1 contributes significantly to increased protein synthesis and hypertrophy induced by resistance exercise . We speculated that resistance training induces both catabolic and metabolic adaptations in skeletal muscle through mTORC1 pathway for the following reasons: (i) Both mTOR‐dependent and ‐independent mechanisms contribute to increased protein synthesis and muscle hypertrophy induced by resistance exercise‐mimicking contractions; (ii) mTORC1 in skeletal muscle is required for normal insulin sensitivity and intramyocellular lipid content, and (iii) Isometric contractions increase Akt phosphorylation and Glut4 translocation to plasma membrane .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from our lab (11, 28), and others (15) suggests that mTORC1 activation in skeletal muscle involves the translocation of mTORC1-lysosome complexes to peripheral regions of the cell (12). Here, we report a similar process by which mTOR-LAMP2 co-localize in the fasted state, prior to mTOR-LAMP2 complex translocation post PRO-CHO ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis was conducted as described previously (28). In short, 5µm sections of muscle tissue were sectioned at -25°C using a Bright 5040 Cryostat (Bright Instrument Company Ltd., Huntingdon, UK) and transferred to room temperature (RT) glass slides (VWR international, UK) and allowed to airdry for ∼1h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation